IWoz computer geek to cult icon : how I invented the personal computer - Wozniak, Steve (New York W.W. Norton & Co, 2006)
Once upon a time, computers looked like big, alien vending machines. They had large screens, cryptic switches, huge boxes, and odd lights. But in 1975, a young engineering wizard named Steve Wozniak had an idea: What if you combined computer circuitry with a regular typewriter keyboard and a video screen? The result was the first true personal computer, the Apple I. Widely affordable and easily understood, Wozniak's invention has been rapidly transforming our world ever since. His life--before and after Apple--is a "home-brew" mix of brilliant discovery and adventure, as an engineer, a concert promoter, a fifth-grade teacher, a philanthropist, and an irrepressible prankster. From the invention of the first personal computer to the rise of Apple as an industry giant, iWoz presents a no-holds-barred, rollicking, firsthand account of the humanist inventor who ignited the computer revolution
Keywords: Wozniak, Steve, 1950-